Charge‐Enriched Strategy Based on MXene‐Based Polypyrrole Layers Toward Dendrite‐Free Zinc Metal Anodes. Issue 13 (9th February 2022) - Zhang, Yongzheng; Cao, Zhenjiang; Liu, Sijin; Du, Zhiguo; Cui, Yanglansen; Gu, Jianan; Shi, Yongzheng; Li, Bin; Yang, Shubin
Abstract: Although zinc metal anodes have some intrinsic advantages for aqueous zinc ion batteries, the notorious dendrites hamper its practical applications. Herein, a charge‐enriched strategy through MXene‐based polypyrrole (MXene‐mPPy) layers is explored toward dendrite‐free Zn metal anode. The MXene‐mPPy layers composed of mesoporous PPy on both sides of Ti3 C2 T x ‐MXene exhibit an exceptional charge enrichment ability (149 F g −1, 5 mV s −1 ), which is beneficial not onlying terms of accumulating the charge levels, but also to homogenize the dispersions of electric field and ion flux as used as an artificial interface on a Zn anode. Thus, a dendrite‐free Zn anode with an ultralong cycling lifespan up to 2500 h and superior rate capability is achieved, which is further applied as an anode for aqueous zinc ion batteries with a long‐term span over 3000 cycles at 10 A g −1 . Abstract : A charge‐enriched strategy through MXene‐based polypyrrole (MXene‐mPPy) layers is explored for zinc anodes. Such MXene‐mPPy layers composed of mesoporous PPy on MXene exhibit an exceptional charge enrichment ability, which is beneficial not only in terms of accumulating the charge levels, but also to homogenize the dispersions of electric field and ion flux, contributing to a dendrite‐free zinc anode with good electrochemical performance.